The Decline of Voter Participation in the 2024 Regional Elections: An Evaluation of KPU Performance and Substantive Democracy in Banyumas, Brebes, and Sukoharjo Regencies - Cahyani, Enny Dwi; Rahmawati, Hikmah; Oktobrian, Dwiki; Basworo, Handityo (Riviera Publishing, 2025)
This research analyzes the decline in voter participation in the 2024 Simultaneous Regional Elections as an indicator of weakening substantive democracy at the local level. Focusing on Banyumas, Brebes, and Sukoharjo Regencies, it evaluates the performance of the regional KPU and the structural-political factors influencing voter engagement. A mixed-methods approach combines quantitative data (participation in the 2018–2024 Regional Elections, empty box and single candidate cases, KPU evaluation scores) with interviews involving KPU members, political parties, journalists, academics, and the public. Field data show participation declined from 74% (2018) to 68–71% (2024). In Brebes, the presence of a single candidate and significant empty box voting indicates dissatisfaction and structural apathy. The Banyumas KPU received an average performance score of ?79 (good), though weaknesses were found in political party candidacy socialization. Literature highlights several causes of declining participation: voter fatigue from overlapping national and regional elections, limited competition caused by single candidate elections leading to structural golput, and weak party mobilization and political communication (DPR RI, 2024; TVOneNews, 2024; CNN Indonesia, 2024; KPU Journal, 2023). Drawing on Dahl’s (1989) democracy framework and Verba et al.’s (1995) theory of participation, this study concludes that while democratic procedures persist, substantive quality is eroding. Recommendations include strengthening community-based and digital socialization by the KPU, revising single candidate regulations, and revitalizing parties’ role in political education.